Exploring the impact of inclusive leadership and exploitative innovation capability on tourism performance - Dian Marlina Verawati; S Suharnomo; Indi Djastuti (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2025)
UNESCO World Heritage Sites face the unique challenge of balancing cultural preservation with the pursuit of organizational performance in an increasingly competitive tourism landscape In the dynamic tourism business environment, competition among tourism destinations has become increasingly fierce, driving the need for innovation and sustainable competitive advantage to achieve superior tourism performance. This study aims to examine the role of inclusive leadership in fostering innovation to enhance organizational performance. Using a saturated sampling technique, data were collected from 110 managers of the Borobudur National Tourism Strategic Area (KSPN) in Central Java, Indonesia. The research employs the SEM-PLS approach to analyze structural equation modeling and predict the research model for theoretical development. The findings contribute to advancements in Dynamic Capabilities Theory by demonstrating that: (1) inclusive leadership and absorptive capacity positively influence exploitative innovation capabilities; (2) exploitative innovation capabilities positively affect both organizational and innovation performance; (3) exploitative innovation capabilities mediate the relationship between inclusive leadership and organizational performance; (4) absorptive capacity positively influences innovation performance; and (5) innovation performance positively impacts organizational performance. These insights provide valuable implications for developing sustainable tourism destinations through leadership and innovation strategies.